The optic nerve sheath in hypertensive disorders of pregnancy and perinatal outcomes: a cohort study - Marina Félix da Mota; Melania Maria de Amorim; Mário Diego Teles Correia; Leila Katz (BMC, 2024)
Abstract Background Preeclampsia is implicated in 14% of maternal deaths worldwide, mostly due to complications such as intracranial hemorrhage and cerebral edema. Cerebral edema increases intracranial pressure, which can be predicted by ultrasonographic measurement of the optic nerve sheath diameter (ONSD). Greater diameters have been reported in women with preeclampsia and eclampsia; however, data are lacking on the possible association with maternal and neonatal adverse outcomes. This study aimed to determine whether there is an association between hypertensive disorders of pregnancy and the ONSD, and between this measurement and maternal and neonatal adverse outcomes. Methods This was a cohort study involving 183 women in the third trimester of pregnancy or within 24 h following childbirth, distributed as follows: control group (n = 30), gestational hypertension (n = 14), chronic hypertension (n = 12), preeclampsia without severe features (n = 12), preeclampsia with severe features (n = 62), superimposed preeclampsia (n = 23) and eclampsia (n = 30). The participants underwent ocular ultrasonography, and data on maternal and neonatal outcomes were collected from the medical records. To compare the groups, analysis of variance was used for the normally distributed numerical variables and the Kruskal-Wallis test was used for variables with non-normal distribution. Two-tailed p-values ≤ 0.05 were considered statistically significant. Results Overall comparison between the seven groups showed no statistically significant difference in the mean ONSD (p = 0.056). Nevertheless, diameters were significantly greater in the eclampsia group compared to the control group (p = 0.003). Greater diameters were associated with maternal admission to the intensive care unit (ICU) (p < 0.01) and maternal near miss (p = 0.01). There was no association between ONSD and admission to the neonatal ICU (p = 0.1), neonatal near miss (p = 0.34) or neonatal death (p = 0.26). Conclusions No association was found between ONSD and the hypertensive disorders of pregnancy in the overall analysis; however, ONSD was greater in women with eclampsia compared to controls. Greater diameters were associated with maternal admission to the ICU and maternal near miss. These findings suggest a potential use for bedside ultrasound as an additional tool for stratifying risk in patients with hypertensive disorders of pregnancy.